1985
DOI: 10.1037/0022-0663.77.6.668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cooperative, competitive, and individualistic goal structures on computer-assisted instruction.

Abstract: The impacts of computer-assisted cooperative, competitive, and individualistic instruction were compared on student achievement and attitudes. Seventy-three eighth graders were randomly assigned to conditions stratified for sex and ability. In all conditions students completed the same computer-assisted instructional unit. The results indicate that computer-assisted cooperative instruction promotes greater quantity and quality of daily achievement, more successful problem solving, and higher performance on fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
6

Year Published

1987
1987
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(75 citation statements)
references
References 14 publications
4
65
0
6
Order By: Relevance
“…This relationship is the very reason why collaborative learning is deployed (Kearsley, 1995;Laurillard, 2002;Lethinen, Hakkarainen, Lipponen, Rahikainen, & Muukkonen, 2001;Vygotsky, 1978). Collaborative learning provides the social context where learners may become actively involved in cognitive processes such as grounding, critical thinking, and knowledge construction, which benefit deep learning and retention of the concepts learned (Biggs, 1987;Johnson et al, 1985).…”
Section: Sociability Influences Social Presence (H S-sp )mentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship is the very reason why collaborative learning is deployed (Kearsley, 1995;Laurillard, 2002;Lethinen, Hakkarainen, Lipponen, Rahikainen, & Muukkonen, 2001;Vygotsky, 1978). Collaborative learning provides the social context where learners may become actively involved in cognitive processes such as grounding, critical thinking, and knowledge construction, which benefit deep learning and retention of the concepts learned (Biggs, 1987;Johnson et al, 1985).…”
Section: Sociability Influences Social Presence (H S-sp )mentioning
confidence: 99%
“…Thus, social interaction is an essential condition for collaborative learning (Johnson, Johnson, & Stanne, 1985). Web 2.0 technologies seem to be a promising vehicle to promote such interactions within CSCL environments.…”
mentioning
confidence: 99%
“…Some studies demonstrate significantly higher achievement for collaborative groups (Dalton et al, 1989;Hooper et al, 1993;Johnson et al, 1985;1986), while others find no significant differences between individuals and small groups (Carrier & Sales, 1987;Makuch et al, 1992;Webb, 1985). Webb (1987) reviewed 14 studies comparing achievement between group and individual computer work and found similar results; only five studies found differences favoring the group activity.…”
Section: Research On Collaborative Learningmentioning
confidence: 71%
“…"Group-to-individual transfer occurs when students...demonstrate mastery of the material being studied on a subsequent test taken individually" (Yager, Johnson, & Johnson, 1985, p. 61). Research on collaborative, computer-based instruction generally supports this assertion; students working collaboratively in computer-based instruction perform as well as students working alone (Carrier & Sales, 1987;Makuch, Robillard, & Yoder, 1992;Webb, 1985; and often perform better (Dalton, Hannafm, & Hooper, 1989;Hooper, Temiyakara, & Williams, 1993;Johnson, Johnson, & Stanne, 1985;1986).…”
Section: Dependent Variablementioning
confidence: 87%
“…et l'effet positif de certains objectifs pédagogiques (présenter un travail à un public, rechercher des informations ou communiquer électroniquement) sur l'effort délibéré d'utiliser cet outil hors classe. Des recherches quantitatives (Johnson, Johnson et Stanne, 1985) et des synthèses (Lou, Abrami et d'Apollonia, 2001) sur le travail en petits groupes avec technologies informatiques montrent que, comparativement à d'autres situations, travailler en groupe coopératif a des conséquences positives sur le plan des acquisitions, des efforts et des attitudes des élèves. Les travaux menés dans le domaine plus précis des CMO montrent que ces dispositifs encouragent les étudiants à réfléchir sur leurs propres points de vue et ceux des autres, les forcent à clarifier leurs pensées par l'écriture et les aident à prolonger leur réflexion (Hara, Bonk et Angeli, 1998;Kang, 1998;Bereiter et Scardamalia, 1992;Sherry, 2000).…”
Section: Introductionunclassified